Urinary incontinence in women - social, medical and scientific problem - Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2003)
Urinary incontinence is noticed by WHO as one of the most important medical problems in XXI century. As human’s population is becoming older the frequency of the disease will be growing and will have more powerful influence on human’s quality of life. Although urinary incontinence is not life-threatening disease, it is serious disability. It removes women from professional, social, and even family life. Simultaneously the issue combined with this disease is poorly understood not only by patients, but many health care providers as well.